Cognitive Impairment and Its Associated Risk Factors in the Elderly With Type 2 Diabetes Mellitus - Suain Bon, Rosnadia; Ariaratnam, Suthahar; Mat Saher, Zanariah; Mohamad, Mariam; Lee, Fatt Soon (Frontiers in Psychiatry, 2021)
Cognitive impairment is not only common but may also act as a precursor for dementia. Moreover, diabetes mellitus has been shown to promote the progression of dementia. This study aims to determine the prevalence of cognitive impairment and its associated risk factors among the elderly patients having Type 2 Diabetes Mellitus (T2DM) in Hospital Kuala Lumpur, Malaysia. This is a cross sectional study involving 113 participants attending the physician clinic. Participants were selected using universal sampling method. Tools included sociodemographic questionnaire, the Montreal Cognitive Assessment, the Depression Anxiety Stress Scale and the Mini-International Neuropsychiatry Interview (M.I.N.I.). Descriptive analysis was performed and followed by multiple logistic regression. The prevalence of cognitive impairment, depressive and anxiety disorders was 46.9%, 10.6% and 2.7% respectively. Indians (aOR = 4.90, CI= 1.57-15.27) as well as participants who had completed their secondary (aOR = 0.34; CI = 0.12-0.96) and tertiary (aOR = 0.05; CI = 0.01-0.26) levels of education were significantly associated with cognitive impairment. The prevalence of cognitive impairment was high as well as significantly associated with ethnicity and education levels of the elderly participants. Indeed, both secondary and tertiary education decreased the odds ratio of developing cognitive impairment when compared with no formal and primary education. To determine and reduce the potential risk factors which contribute to cognitive impairment, early diagnosis of T2DM is crucial. Early detection and treatment of T2DM as well as its associated risk factors are key factors in protecting against cognitive impairment. Keywords: Cognitive Impairment, Elderly, Type 2 Diabetes Mellitus, Depression, Anxiety